SAMDC3 enhances resistance to Barley stripe mosaic virus by promoting the ubiquitination and proteasomal degradation of viral γb protein - Li, Zhaolei (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.